ENDOTHELIAL NITRIC OXIDE SYNTHASE POLYMORPHISM AND ISCHEMIC HEART DISEASES IN COHORT OF EGYPTIAN PATIENTS - NAHLA ANBER,; MAYSAA EL SAYED ZAKI, (International Journal of Pharma and Bio Sciences, 2016)
The aim of the present work was to study the relations between two types ‘of genetic polymorphism of eNOS Glu298Asp and T786C and the presence of coronary artery diseases in cohort of Egyptian patients.The study included 76 patients who were diagnosed to have coronary artery diseases from Mansoura University hospitals and 40 healthy control subjects. Blood samples were obtained for complete lipid profile study and molecular study of genetic polymorphism of nitric oxide synthase Glu298Asp and T786C.The presence of polymorphism of G-Asp was detected in patients in significantly higher rates than control (39.5% &15% respectively, P=0.006). Also, polymorphism T-C was significantly detected in patients compared to control (32.8% & 10% respectively, P=0.03). The study highlights that Glu298Asp and T786C genetic polymorphism of endothelial nitric oxide synthase is a common finding among patients with ischemic heart disease. The presence of polymorphism is associated with dyslipidemia. Further studies are required to establish this finding.